Efficacy Of Fungicides And Bioagents Against Seed Borne Fungi Of Wheat (Journal of Plant Disease Sciences, 2023)
Wheat is an important cereal crop of Indian agriculture and food security system. Seed borne diseases have been found to have an impact on wheat crop plant growth and productivity. Assessment and management of wheat seed borne fungi is an important. A. alternata, C. lunata, D. tetramera, B. sorokiniana were detected and isolated from seed samples by standard blotter paper method. Fungicides were tested in vitro against wheat seed borne fungi using the poisoned food technique. Tebuconazole (0.1%), Carbendazim + Mancozeb (0.25%) and Carboxin + Thiram (0.3%) were found most to be the most effective fungicides, inhibiting 100% of the mycelial growth of all associated seed-borne fungi, followed by Azoxystrobin + Difenoconazole (0.1%). Bioagents were also tested against wheat seed-borne fungi using a dual culture technique, and the results revealed that the fungal bioagent Trichoderma harzianum was found most effective against seed borne fungi, followed by Trichoderma asperellum. Bacterial antagonists were found to be less effective than fungal antagonists.
Keywords: Bioagents; Fungicides; Seed myco-flora; Wheat